Chondromyxoid fibroma of the lumbar spine: case report and literature review - Gutiérrez-González, Raquel; De Reina, Laura; Saab, Anwar; Jiménez-Heffernan, José; García-Uría, José (European spine journal, 2012)
Purpose Chondromyxoid fibroma (CMF) is a benign tumour of the bone that typically occurs in long bone metaphysis. Spinal involvement is uncommon, but more frequent in the cervical and thoracic segments. Lumbar involvement is extremely rare. We report the ninth case of lumbar CMF and the first one involving the articular process of the vertebra. A review of the literature is also intended making special emphasis on the differential diagnosis with other benign spinal tumours of the bone. Methods A 21-year-old Caucasian male suffering from low back pain that increased with sports and interrupted sleep was diagnosed with a tumoural lesion in the right inferior articular process of L5. Results Complete surgical excision of the tumour was accomplished. Histological diagnosis confirmed a CMF. The patient remains asymptomatic at 1-year follow-up. Conclusion Despite the low incidence of CMF in the lumbar spine, differential diagnosis must include this subtype of lesion among other benign tumours of the bone and cartilage. Histological diagnosis is essential in order to provide the patient with an accurate management of the pathology. Recurrence rate is to be considered even in the case of complete surgical excision. Radiotherapy administration is controversial due to suspicion of malignant transformation of the tumour.